94.3k views
4 votes
Simplify-3 + x/2 for x = 6

User Lonna
by
6.3k points

2 Answers

3 votes

Answer:
\boxed{\boxed{0}}

Explanation:

-3+ 6/2 .... this will be simplified.

Remember, x=6.

We first do 6รท2 which equals 3. Then we do -3+3. And that gives us 0.

Answer = 0.



User Kristofer
by
5.6k points
7 votes

Answer:

The value of the expression -3 + x/2 for x = 6 is 0

Explanation:

Let the expression be

f(x) = -3 + x/2

For x = 6 means that substituting the value of x as 6

we get,

f(6) = -3 + 6/2 = -3 +3 = 0

Therefore the value of the expression -3 + x/2 for x = 6 is 0

that is f(6) = 0

User Umesh Patadiya
by
6.2k points